Determination of the Botanical Origin and Physicochemical Properties of a Propolis Sample Through an Integrated Methodology - Jose Juan Alcivar-Saldaña; Marco Aurelio Rodriguez-Monroy; Arturo Aguirre-Gómez; Liborio Carrillo-Miranda; Benjamin Velasco-Bejarano; Maria Margarita Canales-Martinez (MDPI AG, 2024)
The growing interest in products of natural origin has led to the implementation of products such as propolis because they possess biological properties that are useful in the treatment of various ailments, so it is relevant to know the botanical origin of the physicochemical compounds that provide propolis with its biological properties. To identify the floral sources that provide resources to bees for the manufacture of propolis, several methodologies have been implemented, such as palynological analysis, which, through pollen content, has made it possible to identify the plant species that provide resources to bees. On the other hand, analysis of the physicochemical components of propolis has revealed that phenols and flavonoids are mainly responsible for the biological activity of propolis. Evaluation of the antibacterial and antifungal potential of propolis revealed the inhibitory potential of both Gram (+) and Gram (−) bacteria, as well as Candida albicans. However, all these investigations have been carried out individually and not always with the same sample. Therefore, the objective of this research was to design a methodology that allows the use of a single sample of propolis and uses sufficient resources for different research areas to evaluate most of the physical and chemical properties of propolis, as well as its botanical origin. With the implemented methodology, it was possible to obtain sufficient resources that provided results for each of the research areas, taking advantage of the propolis sample.